Capsular serotyping of pasteurella multocida from various animal hosts - a comparison of phenotypic and genotypic methods - Arumugam, N.D.; Ajam, N.; Blackall, P.J.; Asiah, N.M.; Ramlan, M.; Maria, J.; Yuslan, S.; Thong, Kwai Lin (Malaysian Society of Parasitology and Tropical Medicine, 2011)
One hundred and fourteen strains of Pasteurella multocida were isolated from different domestic animals species (cattle, buffalo, sheep, goat, pig, rabbit, dog, cat), avian species (chicken, duck, turkey) and wild animals (deer, tiger, orang utan, marmoset). The serogroups of P multocida were determined by both conventional capsular serotyping and a multiplex PCR assay targeting specific capsular genes. Based on the conventional serotyping method, the 114 strains of P multocida were subtyped into 55 species-specific (untypeable strains) P. multocida, 15 serogroup A, 23 serogroup B and 21 serogroup D. Based on the multiplex PCR assay on the specific capsular genes associated with each serogroup, the 114 strains were further divided to 22 species-specific P. multocida (KMT1 - 460 bp), 53 serogroup A (A - 1,044 bp), 33 serogroup B (B - 760 bp) and 6 serogroup D (D - 657 bp). No serogroup E (511 bp) or F (851 bp) was detected among the Malaysian P. multocida. PCR-based typing was more discriminative and could further subtype the previously untypeable strains. Overall, there was a significant and positive correlation between both methods in serogrouping P. multocida, (r = 0.7935; p < 0.4893). Various serogroups of P. multocida were present among the livestock with 75 of the strains belonging to serogroups A or B. PCR serotyping was therefore a highly species-specific, sensitive and robust method for detection and differentiation of P multocida serogroups compared to conventional serotyping. To the best of our knowledge, this is the first report from Malaysia of the application of a PCR to rapidly define the species-specific P. multocida and its serogroups as an important zoonotic pathogen in Malaysia.